2015
DOI: 10.4085/1062-6050-50.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Muscle Activation in Patients With or Without Chronic Ankle Instability During Walking

Abstract: Context: Ankle sprains are among the most common musculoskeletal injuries, and many individuals with ankle sprains develop chronic ankle instability (CAI). Individuals with CAI exhibit proprioceptive and postural-control deficits, as well as altered osteokinematics, during gait. Neuromuscular activity is theorized to play a pivotal role in CAI, but deficits during walking are unclear.Objective: To compare motor-recruitment patterns as demonstrated by surface electromyography amplitudes between participants wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
4
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 42 publications
(74 reference statements)
7
77
4
6
Order By: Relevance
“…Surface electromyography (sEMG) testing of the peroneal musculature has identified alterations in activation and timing of activation during walking gait [10,65]. More proximal alterations in sEMG have also been identified in the gluteal musculature [66,67] and rectus femoris [67] during walking gait. These alterations have been hypothesized to play a role in force absorption and production and associated plantar pressure research has identified differences in the center of pressure during gait [68].…”
Section: Sensorimotor Function and Ankle Instabilitymentioning
confidence: 98%
“…Surface electromyography (sEMG) testing of the peroneal musculature has identified alterations in activation and timing of activation during walking gait [10,65]. More proximal alterations in sEMG have also been identified in the gluteal musculature [66,67] and rectus femoris [67] during walking gait. These alterations have been hypothesized to play a role in force absorption and production and associated plantar pressure research has identified differences in the center of pressure during gait [68].…”
Section: Sensorimotor Function and Ankle Instabilitymentioning
confidence: 98%
“…Ankle sprains are among the most common musculoskeletal injuries, and many individuals with ankle sprains develop chronic ankle instability (FEGER et al, 2015). Ankle sprains are commonly related to sporty activities and often associated with decreases in sensorimotor control, including proprioception, muscle strength and balance (STEIB et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A more reasonable and effective trajectory can be planned using the measured data of the ankle's 3D motion space [11,12]. In the ankle mechanism, movement in different directions is controlled by different bones, muscles, and ligaments [13,14]. Injured muscles or ligaments could be detected by medical equipment, and targeted therapy and rehabilitation training could be used to achieve better rehabilitation effects [15,16].…”
Section: Introductionmentioning
confidence: 99%